DAGESTAN BLASTERS: HISTORICAL TRADITIONS OF STONE PROCESSING INDUSTRY AND THEIR EVOLUTION IN THE XX CENTURY (According to the materials of the Dargins) - Magomedov, Amirbek Dz.; Usupov, Hizri Abdulmadzidovic (History, Archeology and Ethnography of the Caucasus, 2023)
The crafts of stone processing, crafts of masons of Dagestan in the scientific literature of Dagestan are poorly studied. The ethnographic literature provides information about their work in the context of studying the material culture and house-building of individual ethnic groups of Dagestan. In this regard, the work of P.M. Debirova and M.O. Osmanov, where many features of stone processing crafts are shown. They also highlight the ritual practice of such crafts (customs of mutual assistance in building a house, etc.). At the same time, the sociological aspects of the topic related to the historical evolution of such crafts have been poorly studied. Of great interest in this regard are materials on individual stone processing centers, in particular on the village. Harbuk, in the past a well-known center not only for blacksmiths, but also stone processing crafts.
Keywords: traditional trades and crafts; mason; house building; stone carving; Harbuk village